Endogenous glucose production and gluconeogenesis during exercise in athletes on either a low-carbohydrate or mixed diet - Webster, Christopher Charles (MRC/UCT RU for Exercise and Sport Medicine, 2016)
INTRODUCTION. The LCHF diet produces major changes in whole-body substrate metabolism and energy stores such as reduced muscle and liver glycogen content, increased rates of fat oxidation and decreased rates of carbohydrate (CHO) oxidation. Despite reduced CHO availability, the rate of CHO oxidation that can be sustained during exercise in LCHF athletes is surprisingly high. The most probable source of this glucose is via the process of gluconeogenesis (GNG). However, endogenous glucose production (EGP) and GNG has not been studied during exercise in athletes on a LCHF diet. Therefore, the aim of this study was to determine if there are differences in EGP, GNG and glycogenolysis (GLY) during exercise in endurance-trained athletes who habitually eat either a mixed or LCHF diet. METHODS. Fourteen (7 LCHF, 7 Mix) endurance-trained male cyclists (VO₂max 61 ± 5 ml/kg/min LCHF; 6 3 ± 8 ml/kg/min Mix), matched for age (36 ± 6 y LCHF; 32 ± 5 y Mix), body composition (BMI 23.6 ± 1.8 LCHF; 23.4 ± 2.0 Mix) and relative peak power output (4.8 ± 0.4 W/kg LCHF; 5.0 ± 0.4 W/kg Mix), were recruited. Diets were analysed using the Automated Self-Administered 24-hour Recall (ASA24) analysis software. Participants cycled for 2 h at 55% of peak power output during which EGP was measured by infusion of [6,6- ²H₂ ]glucose, and fractional gluconeogenesis was measured by ingestion of ²H₂O. Blood samples were collected at regular intervals for isotope enrichment analysis. R ESULTS. Rates of GNG were similar during exercise in both the LCHF and mixed diet groups (2.8 ± 0.4 mg/kg/min LCHF; 2.5 ± 0.3 mg/kg/min Mix). The rates of GLY during exercise were significantly higher in the mixed diet group than the LCHF group (3.2 ± 0.7 mg/kg/min LCHF; 5.3 ± 0.9 mg/kg/min Mix) which resulted in significantly higher rates of EGP in the mixed diet group (6.0 ± 0.9 mg/kg/min LCHF; 7.8 ± 1.1 mg/kg/min Mix). There were significant differences in the mean fat oxidation rates (1.2 ± 0.2 g/min LCHF; 0.5 ± 0.2 g/min Mix) and CHO oxidation rates (1.3 ± 0.5 g/min LCHF; 3.1 ± 0.5 g/min Mix). Blood beta-hydroxbutyrate (βHB) concentrations were significantly higher in the LCHF group than in the mixed diet group throughout exercise but there were no differences in plasma glucose, plasma lactate, serum insulin or serum FFA concentrations. The diets of the two groups differed only in fat and CHO intake (%Protein / %Fat / %CHO: 21/72/7 LCHF; 16/33/51 Mix). DISCUSSION. Rates of fat oxidation and CHO oxidation were not associated with the rates of GNG. Apart from βHB, the precursor, substrate and insulin concentrations were remarkably similar in both groups and may have influenced GNG similarly in both groups. We conclude that rates of GNG are relatively stable across a broad range of habitual diets that can significantly alter substrate utilisation, and that dietary CHO modulates the rates of EGP via alterations in rates of GLY, both at rest and during exercise.